2015
DOI: 10.1111/acer.12626
|View full text |Cite
|
Sign up to set email alerts
|

Gender Effects in Alcohol Dependence: An fMRI Pilot Study Examining Affective Processing

Abstract: Background Alcohol dependence (AD) has global effects on brain structure and function, including frontolimbic regions regulating affective processing. Preliminary evidence suggests alcohol blunts limbic response to negative affective stimuli and increases activation to positive affective stimuli. Subtle gender differences are also evident during affective processing. Methods Fourteen abstinent AD individuals (8 F, 6 M) and 14 healthy controls (9 F, 5 M), ages 23 to 60, were included in this facial affective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Accordingly, the saccharin preference test highlighted a greater reduction in sensitivity to natural reward in IAR than in CAR indicating that, although both alcohol-drinking patterns diverted motivational resources in female rats, a prominent drop in interest- or pleasure- into naturally rewarding stimuli occurred in IAR, in favor of a higher alcohol-related salience (Robinson and Berridge, 1993 ). The reduction in reward sensitivity is considered a core symptom of depression, although recent evidence highlights that the alteration of affective processing is not always associated with depressive symptoms in human alcoholics (Padula et al, 2015 ). Accordingly, continuous and intermittent alcohol exposures produce opposite effects in preclinical tests of depressive-like behavior, generating respectively increased immobility in the 1-day forced swim test in rats, and increased swimming in the re-exposure session of the Porsolt-test in mice (Getachew et al, 2010 ; Lee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the saccharin preference test highlighted a greater reduction in sensitivity to natural reward in IAR than in CAR indicating that, although both alcohol-drinking patterns diverted motivational resources in female rats, a prominent drop in interest- or pleasure- into naturally rewarding stimuli occurred in IAR, in favor of a higher alcohol-related salience (Robinson and Berridge, 1993 ). The reduction in reward sensitivity is considered a core symptom of depression, although recent evidence highlights that the alteration of affective processing is not always associated with depressive symptoms in human alcoholics (Padula et al, 2015 ). Accordingly, continuous and intermittent alcohol exposures produce opposite effects in preclinical tests of depressive-like behavior, generating respectively increased immobility in the 1-day forced swim test in rats, and increased swimming in the re-exposure session of the Porsolt-test in mice (Getachew et al, 2010 ; Lee et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A small fMRI study of airplane pilots—individuals with AUD (8 women, 6 men) and healthy controls (9 women, 5 men)—revealed an interactive effect of AUD and sex on brain activation during negative and positive facial affective processing, such that men with AUD demonstrated higher brain activation than control men, whereas women with AUD showed lower brain activation than control women. 103 By contrast, an fMRI study conducted in long-term abstinent individuals with AUD reported sex-related differences in the pattern of brain responsivity to emotional stimuli, with lower activation in the rostral middle and superior frontal cortex, precentral gyrus, and inferior parietal cortex in men with AUD than in control men, whereas higher activation in superior frontal and supramarginal cortices were observed in women with AUD compared to control women. 104 As suggested, these specificities in brain reactivity between men and women during emotional processing may reflect sex-related differences in the emotional mechanisms leading to the development of AUD.…”
Section: Sex Differences In Alcohol Effects On Brain Structure and Fumentioning
confidence: 92%
“…Emotional processing is associated with activity within well-characterized network-based brain circuitries including prefrontal cortex, insula, cingulate cortex, and medial temporal lobe structures including the amygdala (Davidson et al, 1999; Proverbio et al, 2009). In functional magnetic resonance imaging (fMRI) studies measuring AUD-related abnormal brain responses during emotional processing (Beck et al, 2009; Chanraud-Guillermo et al, 2009; Gilman and Hommer, 2008; Heinz et al, 2007), abstinent ALC individuals showed reduced fMRI activation in the amygdala, hippocampus, anterior cingulate, and medial frontal regions in response to viewing stimuli with a negative affective valence, compared to nonalcoholic control (NC) participants (Marinkovic et al, 2009; Padula et al, 2015; Salloum et al, 2007); in response to viewing stimuli with a positive affective valence, the ALC individuals showed an increase in activation in the anterior cingulate cortex, prefrontal cortex, ventral striatum, and thalamus (Heinz et al, 2007). However, little is known about gender-specific persistent influences of alcoholism-related brain activation in response to affective materials, because little research has compared abstinent alcoholic men (ALC M ) and women (ALC W ) compared to nonalcoholic men (NC M ) and women (NC W ) (e.g., Salloum et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To engage the Emotional Integration and Evaluation System, we asked participants to view complex, emotionally meaningful pictures ( aversive , erotic , gruesome , happy – and neutral for comparison), and to rate how the pictures made them feel ( good , bad , or neutral ). We chose stimuli representing the contrasting valences, because findings from previous research indicated that one or more of those emotional categories were sensitive to deficits in emotional processing by abstinent ALC groups compared to NC groups (Heinz et al, 2007; Marinkovic et al, 2009; Padula et al, 2015; Salloum et al, 2007). It should be noted that the behavioral task is not, explicitly, either an emotion judgment task nor an emotion regulation measure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation